Development of particle maipulation and analysis tool for microfluidic device using dielectrophoresis / Wee Wei Hong - Wee, Wei Hong (2017)
Manipulation and analysis of microparticles in a microfluidic device finds wide application in numerous fields such as application in microbiology, drug and medicine assessment, point-of-care for disease diagnosis and microengineering. Different microfluidic devices were designed and developed to meet the needs for every application based on different engineering practices. The principle of electro-kinetics has had great impact in application to particle manipulation as it attempts to move, assembly, rotate, or separate different types of particles by changing their electrical fields. Many types of electro-kinetics are used in particle manipulation such as electrolysis, electro-osmosis, capillary osmosis, diffusiophoresis, dielectrophoresis, and sedimentation potential. In this study, I focus on the application of dielectrophoresis in manipulation of microparticles on a microfluidic device. Microfluidic chips based on a dielectrophoresis (DEP) technique hold several advantages for microparticle manipulation, such as fast result processing, instant deployment of parameters involved, a small amount of sample required, high spatial resolution, and high accuracy of target selection. Conventional dielectrophoresis techniques such as travelling wave DEP, insulative DEP and 2-dimension DEP were studied and compared with the current study in terms of the ease of fabrication, materials used and ease of access. However, there is an unmet need to develop DEP microfluidic chips on different substrates for different applications in a low cost, facile, and rapid way. For example, most existing DEP microfluidic chip fabrication methods are limited to certain substrate materials such as the photolithography technique, which applies primarily to glass, rather than being adaptable. Further, disposable DEP microfluidic devices are preferred due to the potential issues of electrode damage and sample contamination as induced by the electrolyte electrolysis process on the electrode surface in the DEP procedure. This study develops a new facile and low cost method based on a screen-printing technique for fabrication of electrodes of DEP chips on both solid/soft and transparent/non-transparent substrates (i.e., polymethyl-methacrylate (PMMA), poly(ethylene terephthalate) (PET) and A4 paper intended to provide a good base to enhance electro-kinetic devices as research continues. The fabricated PMMA-based DEP microfluidic chip was selected as an example and successfully used to trap and align polystyrene (PS) microparticles in a suspension and cardiac fibroblasts in a cell culture solution, proving the feasibility of the fabricated DEP microfluidic chip for both microparticle and biological cell trapping . The capability of the developed electrode fabrication method shows its compatibility with different kinds of DEP substrates, which could expand the future application field of DEP microfluidic chips, including new forms of point-of-care diagnostics and trapping circulating tumor cells.